The Progress Towards the Development of DHQO Derivatives and Related Analogues with Inotropic Effects - Wu, Y.; Piao, H.-R. (Mini Reviews in Medicinal Chemistry, 2013)
During the course of the past two decades, our group has worked towards the development of increasingly potent inotropic agents by making structural modifications to compounds derived from 3,4-dihydro-2(1H)-quinolinone (DHQO) and related analogues. Herein, we describe the design and synthesis of a new series of DHQO derivatives and the subsequent evaluation of their positive inotropic activity towards left atrium stroke volume in isolated rabbit-heart preparations. Some of these derivatives presented favorable in vitro activities compared with the reference drug, milrinone, and compound 10a, in particular is currently being investigated as a preclinical drug candidate. This review also describes our progress towards the development of DHQO derivatives and related analogues with positive inotropic activities from 1999 to 2013.
Keywords: Positive inotropic activity